Antiaromatic Sapphyrin Isomer: Transformation into Contracted Porphyrinoids with Variable Aromaticity. Issue 1 (1st December 2022) - Li, Qizhao; Ishida, Masatoshi; Wang, Yunyun; Li, Chengjie; Baryshnikov, Glib; Zhu, Bin; Sha, Feng; Wu, Xinyan; Ågren, Hans; Furuta, Hiroyuki; Xie, Yongshu
Abstract: Sapphyrin is a pentapyrrolic expanded porphyrin with a 22π aromatic character. Herein, we report the synthesis of a 20π antiaromatic sapphyrin isomer 1 by oxidative cyclization of a pentapyrrane precursor P5 with a terminal β‐linked pyrrole. The resulting isomer 1, containing a mis‐linked bipyrrole unit in the skeleton, exhibits a reactivity for further oxidation due to the distinct antiaromatic electronic structure, affording a fused macrocycle 2, possessing a spiro‐carbon‐containing [5.6.5.6]‐tetracyclic structure. Subsequent treatment with an acid afforded a weakly aromatic pyrrolone‐appended N‐confused corrole 3, and thermal fusion gave a [5.6.5.7]‐tetracyclic‐ring‐embedded 14π aromatic triphyrin(2.1.1) analog 4 . The cyclization at the mis‐linked pyrrole moiety of P5 played a crucial role in synthesizing the antiaromatic porphyrinoid susceptible to facile transformation to novel porphyrinoids with variable aromaticity. Abstract : An antiaromatic sapphyrin isomer was successfully synthesized based on the unique cyclization at a terminal N‐confused pyrrole unit of pentapyrrane. The specific reactivity associated with the antiaromaticity and confused pyrrole provides chances for constructing novel porphyrinoids with tunable aromaticity.